2019
DOI: 10.1038/s41588-019-0520-x
|View full text |Cite
|
Sign up to set email alerts
|

A framework for tiered informed consent for health genomic research in Africa

Abstract: frican human genome research is advancing rapidly, owing to falling sequencing costs and international interest in African genomic data: the diversity of African genomes can provide novel insights into biological and etiological mechanisms, thereby promoting diagnostic, prognostic and therapeutic advances for populations in Africa and the rest of the world 1,2. Conducting genomic research in Africa can be logistically challenging 3,4 , but equally challenging is recruiting African participants-many of whom hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 30 publications
(11 reference statements)
0
30
0
Order By: Relevance
“…This is in line with previous research and has been identified as a framework tenet for informed consent of genetic research in Africa. 8 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous research and has been identified as a framework tenet for informed consent of genetic research in Africa. 8 …”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 This is especially true of research with complex procedures and involving innovative approaches such as genetics and biobanking. 6 8 Biobanking involves the collection of biological samples, including blood, urine and other human body tissues and fluids. These approaches have the potential to transform healthcare, leading to precision medicine that involves knowing an individual's genomic traits, thus making it easier to guide disease prevention, diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The unique consenting procedure for PGx testing in SSA populations is also noteworthy. It has been suggested that informed consent for African populations needs to be modelled relative to the culture and ethics of the communities and not extrapolated from Western cultures [ 74 , 77 ]. A tiered informed consent involving the use of African colloquialisms to explain hereditary has been suggested for use in African cohorts [ 77 ].…”
Section: Socio-cultural and Ethical Challenges Vis-à-vis Clinicianmentioning
confidence: 99%
“…It has been suggested that informed consent for African populations needs to be modelled relative to the culture and ethics of the communities and not extrapolated from Western cultures [ 74 , 77 ]. A tiered informed consent involving the use of African colloquialisms to explain hereditary has been suggested for use in African cohorts [ 77 ]. Overcoming these observed social and ethical barriers will require collaboration between clinicians, genetic councillors, and research experts to provide robust institutional support for the successful implementation of PGx testing.…”
Section: Socio-cultural and Ethical Challenges Vis-à-vis Clinicianmentioning
confidence: 99%
“…See Nembaware N et al A framework for tiered informed consent for health genomic research in Africa. Nature Genetics 2019 3 . "Tiered informed consent addresses these challenges by providing detailed information about the intended specimen/data use and storage, thus enabling participants to individually select a level of specimen and/or data sharing through responses to specific questions."…”
Section: Methodsmentioning
confidence: 99%